Optimizing Productif Waqf towards Prosperity: Evidence from PWM DIY - Jaya Putra, Budi; Firmansyah, Rizki (Ihtifaz: Journal of Islamic Economics, Finance, and Banking, 2023)
Introduction: Indonesia is a country with a population of 273 million people, but this large population does not guarantee that the level of prosperity is high. The economic challenge facing the country, especially after Covid-19, is economic recovery in social aspects such as poverty and inequality. Yogyakarta Special Region Province contributes to quite high levels of poverty and inequality in Indonesia. Apart from the fiscal policy used by the government, there are aspects that can reduce poverty rates or reduce disparities through community movements by maximizing waqf into productive waqf. Purpose: This research analyzes the main components and multiplier effect of productive waqf managed by PWM DIY. Methodology: The research combines quantitative data and qualitative data. Quantitative data to provide a descriptive description of waqf management and qualitative data were taken using a sample method consisting of 32 of which there were 28 direct and indirect waqf managers and 4 representatives of DIY PWM. Findings: PWM DIY manages 28,552 M2 waqf land where 2,560 AD2 has been established for 20 percent of educational activities from Nursery school - high school, 20 percent for social and religious activities such as mosques and business charities and 60 percent for office or association activities. Based on the AHP method, it shows that productive waqf activities managed by PWM DIY have increased two priorities, namely increased employment opportunities and increasing access to education services. Apart from that, the benefit ratio (RI) value is 1.14 and the Consistency Ratio (CR) is 0.97, which means that DIY PWM activities in managing waqf into productive waqf are consistent and have a positive impact on the beneficiaries both directly and indirectly on the community.